2003
DOI: 10.1677/jme.0.0310047
|View full text |Cite
|
Sign up to set email alerts
|

Functional interference between estrogen-related receptor alpha and peroxisome proliferator-activated receptor alpha/9-cis-retinoic acid receptor alpha heterodimer complex in the nuclear receptor response element-1 of the medium chain acyl-coenzyme A dehydrogenase gene

Abstract: We undertook a study of molecular interference of nuclear orphan receptors. Nuclear receptor response element-1 (NRRE-1) from the human medium-chain acyl coenzyme A dehydrogenase (MCAD) gene promoter was shown to contain three hexamer elements (site 1 through 3) that are known to interact with a number of nuclear receptors including chicken ovalbumin upstream promoter transcription factor (COUP-TF) and estrogen-related receptor alpha (ERRα). We demonstrated that the peroxisome proliferator-activated receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Nuclear receptor response element (NRRE)-1 (À341/À307), a pleiotropic element present in the MCAD gene promoter [9], is known to interact with a number of NHRs including the RXR and estrogen related receptor (ERR). Maehara et al previously reported that the ERR, but not the PPAR, bound to the NRRE-1 as a homodimer or as two independent monomers [10]. Consistent with this report, we also found that the ERRc bound to the NRRE-1, whereas the PPARa (a negative control) did not ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Nuclear receptor response element (NRRE)-1 (À341/À307), a pleiotropic element present in the MCAD gene promoter [9], is known to interact with a number of NHRs including the RXR and estrogen related receptor (ERR). Maehara et al previously reported that the ERR, but not the PPAR, bound to the NRRE-1 as a homodimer or as two independent monomers [10]. Consistent with this report, we also found that the ERRc bound to the NRRE-1, whereas the PPARa (a negative control) did not ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…It is unusual for a nuclear receptor to bind two ERE half site with such wide space in between. Nonetheless, ERRγ has been reported to bind a broad range of sequences, including the monovalent binding sites (Razzaque et al, 2004), whereas ERRα also binds variety of response sequences (Barry et al, 2006;Johnston et al, 1997) including the NRRE-1 of the medium chain acyl-coenzyme A dehydrogenase (MCAD) gene at sites with 14 bases in the middle (Maehara et al, 2003). Recently, Giguere's laboratory demonstrated that a single nucleotide change in ERRα binding site can affect the mode of PGC-1α activation of its target promoters (Barry et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that some peroxisome proliferators, such as butylbenzyl phthalate, a phthalate ester used as plasticizer, are capable of interacting with estrogen receptors (Zacharewski et al, 1998;Fujita et al, 2003), clofibrate is not known to interact directly with estrogen receptors (Ashby et al, 1997). A recent report suggests that gene transcription mediated via estrogen receptor alpha can be attenuated by PPAR␣/RXR␣ compexes that bind to similar DNA elements (Maehara et al, 2003). The ACI rat model provides a valuable model to gain further insights into potential ER-independent events.…”
Section: Discussionmentioning
confidence: 99%